Hello, universe - Kelly, Erin Entrada (Greenwillow Books, an imprint of HarperCollinsPublishers, 2017)
Virgil feels out of place in his crazy-about-sports family. Valencia is deaf, smart, and loves everything about nature. Kaori is a self-proclaimed psychic, whose little sister, Gen, is always following her around. And Chet wishes the weird kids would just stop being so different so that he can concentrate on basketball. They aren't friends. But when Chet pulls a prank that traps Virgil and his pet guinea pig at the bottom of a well, Kaori, Gen, and Valencia begin a quest to find the missing Virgil.